Poly (Glycerol Sebacate)-Based Bio-Artificial Multiporous Matrix for Bone Regeneration - Liang, Bo; Shi, Qiang; Xu, Jia; Chai, Yi-Min; Xu, Jian-Guang (Frontiers in Chemistry, 2020)
In recent years, bone repair biomaterials that combine cells and bioactive factors have been shown to be superior to autologous bone and allogeneic bone implants. However, neither natural nor synthetic biomaterials can possess all desired qualities such as strength, porosity, and biological activity. In this work we used poly(glycerol sebacate) (PGS), a synthetic material with great osteogenic potential, which has attracted more attention in the field of tissue (such as bone tissue) regeneration due to its good biocompatibility and high elasticity. It additionally has the advantage of being able to be regulated by material synthesis in order to match the strength of bone tissue, and can be easily modified, and made functional. However, pure PGS lacks functional groups and hydrophilicity. Therefore, we used PGS as the substrate with which to graft the adhesive ligands RGD and vascular endothelial growth factor mimetic peptide. The bone repair scaffold can be prepared by photo crosslinking, which not only improves hydrophobicity, but also promotes vascularization and accelerates osteogenesis. At the same time, we improved the preparation method of hydrogels after freeze-drying and crosslinking to form a sponge-like structure and easily regenerate blood vessels. In summary, a bone repair scaffold was prepared to meet the structural and biological requirements, and has been proven to serve as a potential bone-mimicking scaffold by enhancing tissue regenerative processes such as cell infiltration, vascularization, and subsequent replacement by native bone tissue.